Family care work: a policy-relevant research agenda. (23rd March 2017) - Moen, Phyllis; DePasquale, Nicole
Abstract : This article addresses the need for policy-relevant research agendas on family care in transaction with formal care and public as well as organisational norms and policies in light of the crisis in caregiving for older adults. We propose a combined institutional and life-course theoretical approach, suggesting seven ways of organising scholarly enquiry to promote understanding of the changing nature of family care in the 21st century, inform policymakers' efforts at supporting family caregivers and improve caregivers' and care recipients' quality of life. These include: (1) moving beyond snapshots of individuals; (2) conducting comparative cross-cultural and crosscohort analyses; (3) documenting social heterogeneity, vulnerability and inequality; (4) capturing individuals' and families' adaptive strategies and cycles of control during the caregiving process; (5) investigating policy innovations and natural experiments; (6) assessing third parties as mediating institutions between regulatory environments and caregiving families; and (7) attending to the subjective meanings of care.